Geochemical study of the Northwest Africa 6148 Martian meteorite and its terrestrial weathering processes. (11th April 2017) - Torre‐Fdez, Imanol; Aramendia, Julene; Gomez‐Nubla, Leticia; Castro, Kepa; Madariaga, Juan M.
Abstract : The number of studies of Mars geology through the geochemical analysis of Martian meteorites has been increasing in the last years because of the amount of information that can be obtained about the planet. In this study, a Martian meteorite, the Northwest Africa 6148 nakhlite, has been analysed and characterised, as there were few studies about it. After analysing it by Raman spectroscopy and Scanning Electron Microscope–Energy Dispersive X‐ray Spectroscopy coupled to the Structural and Chemical Analyser interface, augite and olivine were identified as the main mineral phases of the sample. Moreover, using the Raman bands position, both minerals' metal proportions were estimated. This methodology used in meteorite studies provides good semi‐quantitative results and can offer some advantages to other techniques. In addition, calcite was found, being associated with Earth weathering processes. Surprisingly, Co3 O4 was detected in the matrix of the meteorite. This is the first time that this oxide is observed in a meteorite. It was not possible to determine if it is an original compound from Mars or a product of a weathering process on Earth. However, whichever the case may be, solely the presence of this cobalt oxide represents a relevant finding, as it could provide a deeper knowledge of the Martian geochemistry or the Earth weathering processes. Copyright © 2017 John Wiley & Sons, Ltd. Abstract : In order to characterise the NWA 6148 Martian nakhlite Raman imaging, XRF imaging and SEM‐EDS analysis has been performed. Augite and olivine have been found as the main mineral phases of the sample, and metal proportion quantification was performed by means of Raman bands position for both minerals. Moreover, several uncommon minerals were found, including the Co3 O4, which is the first time that is observed in a Martian meteorite.